Iron ore allocation model to feedstock concentrate plants from multiple sources to multiple destinations considering the uncertainty of grade, in iron ore mines: a case study in Sangan mine, Iran (Rudarsko-geološko-naftni zbornik, 2024)
Operations research is a science that is used in various fields. This science is a set of quantitative techniques that help managers make decisions using scientific methods. This science is related to many axial decision-making issues of managers. For this reason, it is also called the science of management. This science is widely used in industries and mines. One of the most appropriate methods for solving research problems in operations is using linear programming in mining projects. This study was conducted in the Sangan iron ore mine in Iran. In this article, by using linear programming modeling and solving the transportation problem, the allocation of iron ore to feedstock concentrate plants from multiple sources to multiple destinations has been done considering the uncertainty of the grade. This paper is in the field of studying and identifying the quantitative and qualitative amount of extractable iron ore reserves in the mines, and on the other hand, the needs of concentrate plants concerning their feedstock supply by considering the uncertainty of iron ore grade in mines and deciding on their proper allocation. Mineral modeling and estimation of the amount of extractable minerals have been done using the block model. Uncertainty of iron ore grade in the block model is investigated using the sequential Gaussian simulation method. The amount of mining capacity and its sequence is planned considering the type of iron ore used in the plans during 5-year periods. In this article, the modeling of the problem has been done by considering the existing limitations in mines, such as the amount of supply, grade of iron ore, iron oxide and sulfur. On the other hand, the limitations in plants, such as demand, type and grade of iron ore, iron oxide and sulfur are considered in the modeling. In the end, the amount of iron ore tonnage sent from each mine to each plant during 5 years is presented by solving the problem.